Justifying Christian Aramaism. - Staalduine-Sulman, E. van. (Jewish and Christian Perspectives Series, 2017)
In Justifying Christian Aramaism Eveline van Staalduine-Sulman explores how Christian scholars of the sixteenth and early seventeenth century justify their study of the Targums, the Jewish Aramaic translations of the Hebrew Bible. She focuses on the four polyglot Bibles - Complutum, Antwerp, Paris, and London -, and describes these books in the scholarly world of those days. It appears that quite a few scholars, Roman-Catholic, protestant, and Anglican, edited Targumic books and translated these into Latin. The book reveals a stimulating and conflicting period of the Targum reception history and is therefore relevant for Targum scholars and historians interested in the history of Judaism, Church history, the history of the book, and the history of Jewish-Christian relationships.